Результати впровадження індивідуалізації фізичного виховання школярів = Increasing the level of physical fitness of adolescents in the individualization of physical education - L. Levandovska (Kazimierz Wielki University, 2015)
Levandovska L. Результати впровадження індивідуалізації фізичного виховання школярів = Increasing the level of physical fitness of adolescents in the individualization of physical education. Journal of Education, Health and Sport. 2015;5(8):487-506. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.32092 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A487-506 https://pbn.nauka.gov.pl/works/656516 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.07.2015. Revised 05.08.2015. Accepted: 24.08.2015.   РЕЗУЛЬТАТИ впровадження індивідуалізації фізичного виховання школярів Increasing the level of physical fitness of adolescents in the individualization of physical education   L. Levandovska Левандовська Л. Ю.   Кременецький педагогічний коледж Кременецької обласної гуманітарно-педагогічної академії ім. Тараса Шевченка   Анотація   Мета роботи - вивчити функціональний стан кардіореспіраторної системи підлітків у процесі індивідуалізації фізичного виховання. У дослідженні взяло участь 148 підлітків загальноосвітніх шкіл м. Кременця, з них 70 дівчат і 78 хлопців, яких методом рандомізації розподілили на контрольні та основні групи. Завдяки застосуванню запропонованої програми індивідуалізації фізичного виховання у школярів основної групи вдалося суттєво підвищити функціональні можливості кардіореспіраторної системи організму, що наглядно демонструє значне покращення (р<0,05) проби Сєркіна (на 0,8), індексу Скібінскі (на 32,29), показників проб Штанге (на 31,15 сек.) та Генчі (на 15,43 сек.).   Ключові слова: підлітки, функціональний стан, індивідуалізація, підвищення.   L. Levandovska Increasing the level of physical fitness of adolescents in the individualization of physical education Summary   Physical fitness of the younger generation today is recognized as an important component of health, physical development, high performance foundation, preparation for socially useful work. Objective: to study physical fitness of adolescents during physical education classes during the school year. To determine the effectiveness of the proposed individualization of physical training of teenagers was the comparative pedagogical experiment. This study was conducted on the bases Kremenets boarding school and secondary school pupils of 6-7 classes of children age: 11-12 years. Overall in the study participated 148 adolescents, including 70 girls and 78 boys. During the academic year studied the level of physical fitness of students 11-12 years in the individualization of physical education.   Key words: adolescents, physical fitness, individualization, increase.